Improving knowledge about sepsis 3 definition in critically ill patients: new insights - Martínez, María Luisa; Ruiz-Rodríguez, Juan Carlos; Ferrer, Ricard (Journal of Emergency and Critical Care Medicine, 2018)
Sepsis continues to be an important global public health problem with persisting elevated mortality rates. The reported incidence of sepsis is increasing, but considerable international variation in incidence (6–27%) of sepsis has been reported (1-4).